Production Of Citronellol As An Artificial Flavour Using Whole Cell Saccharomyces Cerevisiae : Design Of A Continuous Closed-Gas-Loop Bioreactor For Biotransformation (CCGLBB). - Uzir, Hekarl; Mat Don, Mashitah; Ariffin, Aimi Aishah (Universiti Sains Malaysia, 2008)

(untitled)
The production of artificial flavors with highly chemo-, regio and stereo specific compounds has become an important requirement in food industry. Production of artificial flavors by chemical catalysis has been used previously in converting a reactant into a useful product as a substitute to the natural sources.